Redução de custos e aumento de qualidade em serviços com aplicação de ferramentas de melhoria contínua em operações logísticas: um estudo de caso sobre a Avon Cosméticos entre os anos de 2015 e 2017 - Medeiros, Fabio Antonio (2018)
Large corporations have intensified the optimization of their logistics networks, understanding the strategic importance that the operations area has not only related to the resources release through cost reduction, but also in value generation through the services provided to its customers. This movement brought with it a broad technological development for distribution and logistics operations. As far as automation is concerned, there is a significant evolution, especially in the internal processes of distribution centers, such as: intelligent systems for guarding and withdrawing products, forklift operations without human crew, mechanized loading and unloading of trucks, automated separation of orders and machines for assembly and boxes closing, among other examples. However, there is not a wide range of case studies on operations, which are already automated, that have raised their levels of productivity and quality significantly, without capital investments, but through processes redesign and the performance of operational leadership. This work, therefore, aims to capture and demonstrate what has been done to achieve significant gains in productivity and quality in logistics operations through this union: tools for continuous improvement and leadership performance, without significant use of capital capex. The research problem is then focused on capturing and demonstrating implemented initiatives during the transformation by which this company's distribution process passed related to its logistic activities, as well as the continuous improvement tools used. To do so, a case-study of the logistics operations of Avon Cosmetics in Brazil, between the years of 2015 and 2017, was carried out. As a result, it is expected to detail these projects and initiatives implemented as well as the methodologies or tools applied, the improvements obtained and the connection between theory and practice. As a contribution of this work, it is hoped to reinforce the existing theory on continuous process improvement, thus contributing to the academic and business worlds regarding to operations optimization.